Orality and performance in classical Attic prose : a linguistic approach - Vatri, Alessandro (Oxford classical monographs, 2017)
This work discusses whether there is a linguistic difference between classical Attic prose texts intended for public oral delivery and those intended for written circulation and private performance, establishing a rigorous methodology for the reconstruction of the native perception of clarity in the original contexts of textual reception